Prioritization of pollution potential zones for conservation activities of a lake system. Issue 3 (14th October 2016) - Moses, Sheela A.; Janaki, Letha; Joseph, Sabu; Joseph, Justus; Thomas, Jobin; Lal, Pramod
Abstract: Many coastal lakes are under serious threats due to increased pressures associated with population growth, accelerated eutrophication, invasive species and toxic contamination. The extent of the pollution depends almost entirely on the characteristics and processes taking place in the lake basin. The objective of this study was to identify the pollution potential zones (very high, high, medium and low) in the Akkulam–Veli (A–V) Lake Basin (Thiruvananthapuram, Kerala) using GIS‐enabled, multithematic overlay analysis. The primary characteristics considered were geomorphology, lithology, land use, soil, slope and population density. The results of this study indicated the major portion of the lake basin exhibits very high or high pollution potential zones, with the drains passing through the very high pollution potential zone being mainly responsible for the contamination of the lake water. High population density, predominant commercial use and settlement with mixed tree crop, level and gentle slope (low slope) are the factors responsible for the very high pollution potential. The organic pollutants in the lake system increase with the increased extent of the very high pollution potential area. This analysis approach will help authorities to identify the underlying causes of lake water quality degradation and plan and implement effective measures for protecting the lake. This process can also be utilized by scientists elsewhere to facilitate lake protection.